VALUE OF PANCASILA STUDENT PROFILE IN CATUR PRAMANA LEARNING MODEL - I Komang Wisnu Budi Wijaya; Ni Wayan Satri Adnyani (International Journal of Instructions and Language Studies, 2023)
The information age brings humans to live in uncertainty and unpredictable change. Therefore, to prepare competitive graduates, the government has prepared a curriculum known as the Merdeka Curriculum. The main aim of the Merdeka curriculum is to form a Pancasila student profile. Talking about learning, Hinduism recognizes a way of learning or acquiring knowledge known as Catur Pramana. In this article, the value of the Pancasila student profile contained in Catur Pramana-based learning will be analyzed as literature research. The research stages consisted of collecting literature, reviewing the collected literature, sorting library sources according to the research objectives, analyzing data and drawing conclusions. The data analysis technique was carried out using content analysis techniques. The research results show that all the values of the Pancasila student profile are contained in the Catur Pramana learning model.